Land Subsidence Analysis Using The DinSAR Method in Snap Application for The 2021 Periode - Mairizwan; Hanifah Nur Ismail; Joko Widodo (Department of Physics, Universitas Negeri Padang, 2023)
Three main factors can accelerate the rate of land subsidence, including: natural conditions (geology), groundwater extraction and building mass. Excessive groundwater extraction is believed to be one of the main factors leading to land subsidence. This occurs because there are still many DKI Jakarta residents who have not switched to using PAM RT water (Household Drinking Water Management). Data processing to obtain information in the form of the value of the range of subsidence of the DKI Jakarta area during 2021. The data taken in the form of Sentinel 1A data is then analyzed with the SNAP application using the Differential Interferometry Synthetic Aperture Radar (DInSAR) method. This research is useful to determine the rate of land subsidence in the DKI Jakarta area in 2021. Based on the results of data processing that has been done using the DInSAR method in the ESA SNAP application using Sentinel 1A imagery with data for the DKI Jakarta area in 2021, it can be concluded that for one year in 2021 the results of the decline in the area are -0.7 cm - -2.3 cm which is located near the Jakarta sea waters for one year in 2021.